Adenovirus transcription. II. RNA sequences complementary to simian virus 40 and adenovirus 2DNA in AD2+ND1- and AD2+ND3-infected cells. - Flint, S J (1975)
The genomes of the two nondefective adenovirus 2/simian virus 40 (Ad2/SV 40) hybrid viruses, nondefective Ad2/SV 40 hybrid virus 1 (Ad2+ND1) and nondefective hybrid virus 3 (Ad2+ND3), WERE FORMED BY A DELETION OF ABOUT 5% OF Ad2 DNA and insertion of part of the SV40 genome. We have compared the cytoplasmic RNA synthesized during both the early and late stages of lytic infection of human cells by these hybrid viruses to that expressed in Ad2-infected and SV40-infected cells. Separated strands of the six fragments of 32P-labeled Ad2 DNA produced by cleavage with the restriction endonuclease EcoRI (isolated from Escherichia coli) and the four fragments of 32P-labeled SV40 DNA produced by cleavage with both a restriction nuclease isolated from Haemophilus parainfluenzae, Hpa1, and EcoRI were prepared by electrophoresis of denatured DNA in agarose gels. The fraction of each fragment strand expressed as cytoplasmic RNA was determined by annealing fragmented 32P-labeled strands to an excess of cellular RNA extracted from infected cells. The segment of Ad2 DNA deleted from both hybrid virus genomes is transcribed into cytoplasmic mRNA during the early phase of Ad2 infection. Hence, we suggest that Ad2 codes for at least one "early" gene product which is nonessential for virus growth in cell culture. In both early Ad2+ND1 and Ad2+ND3-infected cells, 1,000 bases of Ad2 DNA adjacent to the integrated SV40 sequences are expressed as cytoplasmic RNA but are not similarly expressed in early Ad2-infected cells. The 3' termini of this early hybrid virus RNA maps in the vicinity of 0.18 on the conventional SV40 map and probably terminates at the same position as early lytic SV40 cytoplasmic RNA. Therefore, the base sequence in this region of SV40 DNA specifies the 3' termini of early messenger RNA present in both hybrid virus and SV40-infected cells.